2020
DOI: 10.1142/s0219455420500893
|View full text |Cite
|
Sign up to set email alerts
|

Damping Characteristics of Bending Vibration of Thick-Walled CFRP Hollow Shafts

Abstract: The damping characteristics of the composite thick-walled hollow shaft directly affect its amplitude of rotational vibration at low speeds and stability at high speeds. In this study, the shaft is made of carbon fiber reinforced plastic (CFRP) material. In order to study the damping characteristics of the composite hollow shaft, a 3D numerical damping model was established based on finite element method and strain energy expression. In this regard, both the contributions of in-plane and out-of-plane strain ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Equivalent damping coefficient of the composite shaft. Previous research on the damping loss factor of composite shafts 30 showed that composite shafts also have orthotropic properties in terms of bending damping. The specific damping capacity (SDC) matrix can be used to describe each composite layer.…”
Section: Equivalent Coefficient Of the Composite Shaftmentioning
confidence: 99%
See 1 more Smart Citation
“…Equivalent damping coefficient of the composite shaft. Previous research on the damping loss factor of composite shafts 30 showed that composite shafts also have orthotropic properties in terms of bending damping. The specific damping capacity (SDC) matrix can be used to describe each composite layer.…”
Section: Equivalent Coefficient Of the Composite Shaftmentioning
confidence: 99%
“…The smaller orientation angle is beneficial in improving the bending stiffness of the composite shaft, while the 6 45°layers maximize the damping ratio. 30,32 . Therefore, in this paper, 6 15°, which has the greatest effect on stiffness enhancement, and 6 45°, which makes the greatest contribution to damping, are selected as the typical fiber orientation angles for design of the laminate schemes.…”
Section: Analysis Of Nonlinear Dynamic Characteristicsmentioning
confidence: 99%